The private autonomy and contract - Leyva Saavedra, José (2011)
Without a doubt, one of the institutions that sets the pace for the development of private law is the formerly called free will, better known today as private autonomy; in other words the freedom of private individuals, acknowledged by the law, to regulate their own legal relations as they wish. As mentioned previously, the law reduces the surface of existential liberty and restores the organized and stipulated legal freedom of the persons to pursue their own objectives, but within the limits set by each legal order. The aforementioned liberty is considered one of the fundamental rights of persons which is best embodied in the contract and its autonomy. Even though it is considered a key part of private legal relations, private autonomy has no specific or explicit space in State constitutions, which is cause for concern, because the laws prefer to grant a constitutional capacity to one of the expressions of such autonomy, which is the contractual freedom.